PipeThreader: Software-Defined Pipelining for Efficient DNN Execution - Cheng, Yu; Wang, Lei; Shi, Yining; Xia, Yuqing; Ma, Lingxiao; Xue, Jilong; Wang, Yang; Mo, Zhiwen; Chen, Feiyang; Yang, Fan; Yang, Mao; Yang, Zhi (OSDI, 2025)
To effectively utilize heterogeneous specialized hardware units in modern GPUs, such as TensorCores and Tensor Memory Accelerators, this paper introduces PipeThreader, a new DNN compiler. PipeThreader proposes shifting scheduling functionality from hardware to software so as to enable more efficient and sophisticated computation pipelining with minimal manual effort. This is achieved through sTask-graph, a new DNN computation abstraction, a hierarchical hardware abstraction that captures the capabilities of specialized units, and new scheduling primitives. As a result, PipeThreader can discover efficient pipeline scheduling for well-studied DNN architectures like FlashAttention, achieving comparable or even superior performance. Additionally, it can uncover novel pipeline schemes for emerging models like Mamba2, delivering significantly better performance compared to state-of-the-art hand-crafted implementations. The code is open-sourced at https://github.com/tile-ai/tilelang.